The COVID-19 Hoax News in Indonesia Context: Looking Beyond the Essence Using Content Analysis - Yusri, Yusri; Rivai, Mantasiah; Anwar, Muhammad (REiLA : Journal of Research and Innovation in Language, 2022)
The hoax has been widely discussed in many studies employing various approaches, and one of the hoaxes massively spread recently is news about COVID-19. This qualitative study aims at investigating the essence of hoax news related to COVID-19 in the Indonesian context using a content analysis approach. The main source of data was 50 hoax news collected from turnbackhoax.com, which is one of the credible anti-hoax news sources in Indonesia. The present study collected the news from 1st January 2022 until 30th March 2020. They were then analysed and interpreted qualitatively. The research findings revealed that hoax news circulated during this pandemic era mostly had the purpose of sparking public panic, especially panic buying and panic moving. To trigger such a condition, writers of hoax news frequently used symbols such as time markers (time signals) and quantifiers and involved famous figures. This implies that hoaxes are not only spread during political events or other important occasions but also when most humans in the world experience mass trauma, which in this case is due to the COVID-19 pandemic.